Advancing methods for biomolecular crystallography - Urzhumtsev, Alexandre G.; Lunin, Vladimir Y.; Read, Randy (NATO Science for Peace and Security Series A: Chemistry and Biology,, 2013)
This work presents a snapshot of the state of the art of modern biomolecular crystallography, from crystallisation through structure determination and even interactive presentation on the web.  Methods driving the latest automated structure determination pipelines are explained, as well as how to deal with problems such as crystal pathologies that still demand expert analysis.  These methods are illustrated through their application to problems of great biological interest, such as the molecular machinery underlying the complement pathway, the mechanism of action of monoamine oxidase inhibitors, and the structure of the eukaryotic ribosome.  Complementary approaches, such as neutron diffraction, small angle X-ray scattering, coherent diffraction and computational modelling, are also explored.